2001
DOI: 10.1096/fj.01-0338fje
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor induces manganese‐superoxide dismutase expression in endothelial cells by a Racl‐regulated NADPH oxidase‐dependent mechanism

Abstract: Vascular endothelial growth factor (VEGF) is a potent vascular endothelial cell-specific mitogen that modulates endothelial cell function. In the present study, we show that VEGF induces manganese-superoxide dismutase (MnSOD) mRNA and protein in human coronary artery endothelial cells (HCAEC) and pulmonary artery endothelial cells. VEGF-mediated induction of MnSOD mRNA was inhibited by pretreatment with the NADPH oxidase inhibitors, diphenyleneiodonium (DPI), and 4-(2-aminoethyl)-benzenesulfonyl fluoride, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 72 publications
5
112
0
2
Order By: Relevance
“…It has been demonstrated that small amounts of ROS are produced after cell stimulation with a variety of hormones and growth factors, including VEGF, following binding to cell membrane receptors [43]. Low concentrations of ROS may even mimic the action of growth factors [44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that small amounts of ROS are produced after cell stimulation with a variety of hormones and growth factors, including VEGF, following binding to cell membrane receptors [43]. Low concentrations of ROS may even mimic the action of growth factors [44].…”
Section: Discussionmentioning
confidence: 99%
“…Western and Northern Blot Analyses-Immunoblot assays were performed by modification of the procedure previously described (55). Briefly, CASMC were washed in phosphate-buffered saline twice and harvested by scraping in 20 mM Tris-HCl (pH 7.5), 150 mM NaCl, 1 mM EDTA, 1 mM EGTA, 1% Triton X-100, 20 mM ␤-glycerophosphate, 10 mM sodium pyrophosphate, 10 mM sodium vanadate, 1 g/ml leupeptin, 1 mM NaF, and 1 mM phenylmethylsulfonyl fluoride, and protease inhibitor mixture (Roche Applied Science).…”
Section: Methodsmentioning
confidence: 99%
“…The signals were quantified with Image (National Institutes of Health), and statistical analyses were carried out using the Student t test. Cell migration assays were carried out by modified Boyden chamber, as previously described (20).…”
Section: Methodsmentioning
confidence: 99%